Women's experience of termination of a pregnancy - M Poggenpoel; CPH Myburgh (AOSIS, 2006)
In November 1996 the Act on the Termination of Pregnancies (no 92 of 1996) was promulgated. This Act enabled women from the age of twelve years old to decide to terminate their pregnancies before twelve weeks gestation without permission of anybody else. Since February 1997 almost 160 000 terminations of pregnancy have been carried out in South Africa. Little research has been conducted to explore and describe the effect of the termination of pregnancies on women Two aims were formulated for the research project described in this article: (1) the exploration and description of the women's experience of terminating a pregnancy, and (2) the description of counselling guidelines for caring professionals to assist these women. Participants were included in the sample through purposive sampling. Phenomenological interviews were conducted individually. Data were analysed by means of Tesch's descriptive approach. Counselling guidelines for educational psychologists and other caring professionals to empower the involved were being logically inferred from the results of the interviews. Measures to ensure trustworthiness have been applied in the research and ethical measures have been strictly adhered to during the research. One central theme was identified from the results of the interviews and naïve sketches, namely women's experiences of a negative relationship with themselves and other persons as well as their focus on their terminated pregnancies.